2010
DOI: 10.3109/09513590903184126
|View full text |Cite
|
Sign up to set email alerts
|

Secondary amenorrhoea with high inhibin B level caused by parasitic ovarian leiomyoma

Abstract: A 35-year-old patient attended the clinic after 1 year of primary infertility and 9 years secondary amenorrhoea. Her BMI was 21.9 kg/m². Transvaginal scan examination showed a small uterus with 1.7 mm thick endometrium. The left ovary was quiescent and measured 2.9 cm x 61.2 cm x 62.1 cm. 3D images manipulation showed a large (96.9 cm³) solid mass attached to the right ovary. Follicle stimulating hormone (FSH) level was 3.8 IU/l, oestradiol was 57 pmol/l and testosterone was 0.9 nmol/l. She had normal thyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Abdulwahid and associates reported parasitic fibroids in a 46-year-old lady without previous history of surgery [10]. This is similar to cases reported by Mushtaq [11] and Abdel-Gadir et al [12]. Previous surgery (laparoscopy) may not be the most significant risk factor for development of parasitic fibroids as stated by many authors.…”
Section: Discussionsupporting
confidence: 78%
“…Abdulwahid and associates reported parasitic fibroids in a 46-year-old lady without previous history of surgery [10]. This is similar to cases reported by Mushtaq [11] and Abdel-Gadir et al [12]. Previous surgery (laparoscopy) may not be the most significant risk factor for development of parasitic fibroids as stated by many authors.…”
Section: Discussionsupporting
confidence: 78%
“…Zaitoon reported a PL in a 40 year old female with morbid obesity without previous abdominal or pelvic operaion [1] . Abdel-Gadir et al reported a 35 year old female presented with PL apart from secondary infertility, she has not past medical or surgical history [6] . Schaudien and his colleagues reported a 70 × 28 × 35 centimeters in size and 41 kg in weight PL in a 16-year-old Hanoverian male [22] .…”
Section: Discussionmentioning
confidence: 99%
“…However PL occurring in virgin abdomen cannot be explained by this etiology. PL is an extremely rare disease with less than 30 reported cases in literature [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] . In line with SCARE guide line, we report a rare case of PL occurring a in a middle age female without history of previous abdominal operation with a brief review of literature [21] .…”
Section: Introductionmentioning
confidence: 99%
“…Several series have described the characteristics of postoperative or iatrogenic parasitic leiomyomas [1] , [2] , [3] . Several other reports have described the occurrence of parasitic leiomyomas in patients without pelvic surgery [4] , [6] . In our patient, the prior history of ipsilateral laparoscopic oophorectomy probably contributed to the development of parasitic leiomyoma.…”
Section: Discussionmentioning
confidence: 95%
“…Parasitic leiomyomas are considered to be pedunculated subserosal uterine leiomyomas which have lost attachment to the uterus, and have adhered to and gained blood supply from other adjacent organs. They can be found anywhere in the abdomen and pelvis, and have been reported in the omentum [4] , [5] , the ovaries [6] , and in the bowel [7] . Lete et al published the first systematic review on parasitic leiomyomas in 2016 [3] .…”
Section: Discussionmentioning
confidence: 98%